The Concept of Wali Hakim, Marriage Witness, and Ijab Kabul in the Book of Al-Nikah: Analysis and Relevance to the Contemporary Context - Firdaus, Firdaus (Civiliza Publishing, 2024)
The purpose of this study is to analyze the concept of wali hakim, marriage witness, and ijab kabul in the Book of Al-Nikah by Sheikh Muhammad Arsyad al-Banjari and its relevance to the current context. The method used in this study is library research. The results of this study indicate that in the Book of Al-Nikah, the concept of wali hakim has 10 conditions that allow the transfer of guardian aqrab to guardian judge. In terms of marriage witnesses, it is explained that there are 13 conditions that must be met by marriage witnesses. In terms of ijab kabul, the meaning of ijab and the meaning of kabul in the marriage contract are explained and a guide to ijab kabul that is applicable to the Banjar community is provided. The three discussions as a whole are in accordance with the opinions of Syafi'iyah scholars and make it easier for the Banjar community at that time to practice them. In the current context, the majority of provisions related to wali hakim in the Book of Al-Nikah are still relevant, although some provisions such as wali aqrab who are hindered by distance and are in prison can be overcome with technological advances and Extraordinary Permits to Leave Prison. Meanwhile, regarding the marriage witnesses and the ijab kabul in the Al-Nikah Book, it can be said that everything is still relevant and even more detailed and practical than the current provisions.